AN ASSESSMENT OF IMPACT AND ADAPTATION STRATEGIES TO CLIMATE CHANGE BY LOCAL INDIGENOUS FARMERS OF MICHIKA LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Williams, James J.; Dunnamah, Albert Y.; Kwale, Joel M. (European Scientific Journal, ESJ, 2015)
The aim of the study is to assess the impact and adaptation strategies to climate change by the local indigenous farmers in Michika Local government Area of Adamawa State, Nigeria. The data of this study were collected using a structured questionnaire survey to 369 local indigenous farmers from the 8 district of the study area. 21 years of rainfall and temperature data were also obtained from the Adamawa State Agricultural Development Programme, Michika. The data collected were analyzed using descriptive statistics in terms of tables, percentage, and trend analysis of rainfall and temperature. The rainfall and temperature trend for the study area showed an increasing trend. The respondents are aware of the impact of climate change, and as such, they mentioned loss of soil fertility (23%), low yields of crops (170%), ease spread of pest and disease (14%), and flood and erosion (13%). The local indigenous farmers employed adaptation strategies such as planting early maturing crops (26.2%), planting resistant crops to pest and drought (22.7%), mixed farming (23.3%), and the intensive use of fertilizer (17.8%). However, constraints towards adaptation according to the respondents includes the lack of adequate knowledge on how to cope with adaptation (16.2%), limited access to improve crop varieties (18.6%), high cost of fertilizers and other farm inputs (19.2%), and the lack of financial resources (17.8%). Chi-square was used to assess the association for the indigenous farmer’s level of awareness of climate change and socioeconomic variables (gender, age, education, qualification, and farming experience). Therefore, all the calculated values mentioned respectively is greater than the critical value (Table 5,6,7,8) at a significance level of 0.05. In addition, we reject Ho and accept H1. Hence, there is association between all the socio-economic variables and climate change in the study area.